The Influence of Work Motivation and Work Environment on Employee Productivity at Sapadia Pematangsiantar - Togar Naibaho; Syah Paradiba Sari Sirait; Winfrontstein Naibaho (CV. Civiliza Publishing, 2026)
This study analyzes the influence of work motivation and work environment on employee work productivity at Sapadia Hotel Pematangsiantar using an inferential quantitative approach, with a total of 60 respondents selected through a saturated sampling technique. Data were collected using structured questionnaires measured on a Likert scale and tested for validity and reliability prior to analysis. Statistical analysis was conducted using multiple linear regression, including t-tests, F-tests, and the coefficient of determination (R²). The results indicate that work motivation has a positive and statistically significant effect on work productivity (β = 0.421; t = 3.87; p < 0.001). Similarly, the work environment exerts a positive and significant influence on work productivity (β = 0.356; t = 3.12; p = 0.003), as evidenced by the F-test results (F = 28.64; p < 0.001). The coefficient of determination (R² = 0.57) reveals that 57% of the variation in employee work productivity is explained by work motivation and work environment, while the remaining 43% is influenced by other factors not examined in this study. These confirm that enhancing employee motivation and improving the quality of the work environment play a critical role in increasing workforce productivity.